Delayed Critique: On Being Feminist, Time and Time Again - McKenna, Emma (Atlantis, 2016)
In this article, I argue for a systematic critique of transphobia in feminism, advocating for a reconciling of trans and feminist politics in community, pedagogy, and criticism. I claim that this critique is both delayed and productive. Using the Michigan Womyn’s Music Festival as a cultural archive of gender essentialism, I consider how rereading and revising politics might be what is “essential” to feminism.